2011
DOI: 10.1099/mic.0.047191-0
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the glucose-inducible outer-membrane protein OprB during utilization of aromatic compounds and organic acids in Pseudomonas putida CSV86

Abstract: Pseudomonas putida CSV86 shows preferential utilization of aromatic compounds over glucose. Protein analysis and [ 14 C]glucose-binding studies of the outer membrane fraction of cells grown on different carbon sources revealed a 40 kDa protein that was transcriptionally induced by glucose and repressed by aromatics and succinate. Based on 2D gel electrophoresis and liquid chromatography-tandem mass spectrometry analysis, the 40 kDa protein closely resembled the porin B of P. putida KT2440 and carbohydrate-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 57 publications
(92 reference statements)
2
26
0
Order By: Relevance
“…The unique property of CSV86 is its ability to utilize aromatic compounds preferentially to glucose and co-metabolism of aromatic compounds and organic acids [10]. Aromatic and organic acidmediated repression of OprB (an outer membrane pro-tein that allows the passage of sugar molecules across the outer membrane) [11], periplasmic glucose-binding protein (ppGBP) [12] and the glucose-metabolizing enzyme Zwf [13] was found to be responsible for this ability. In addition, identification of genes encoding various components of the glucose uptake system (which includes OprB, GBP and three subunits of the ATP binding cassette (ABC) transporter) [9] led us to hypothesize the presence of a high-affinity GBP-dependent ABC transporter in P. putida CSV86.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique property of CSV86 is its ability to utilize aromatic compounds preferentially to glucose and co-metabolism of aromatic compounds and organic acids [10]. Aromatic and organic acidmediated repression of OprB (an outer membrane pro-tein that allows the passage of sugar molecules across the outer membrane) [11], periplasmic glucose-binding protein (ppGBP) [12] and the glucose-metabolizing enzyme Zwf [13] was found to be responsible for this ability. In addition, identification of genes encoding various components of the glucose uptake system (which includes OprB, GBP and three subunits of the ATP binding cassette (ABC) transporter) [9] led us to hypothesize the presence of a high-affinity GBP-dependent ABC transporter in P. putida CSV86.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to ttGBP, in the ppGBP model, loop 2 (amino acids 375-382) and the a-helix (amino acids 200-206) were found to be intact and located at a similar position, while loop 1 was distorted. Superimposition of ppGBP model onto the structure of ecMBP suggested that the loop of ecMBP (amino acids [11][12][13][14][15][16]) that hampers glucose binding was wide enough in ppGBP (amino acids [35][36][37][38][39][40][41] to accommodate a glucose molecule (Fig. 4E).…”
Section: Molecular Modeling and Identification Of Putative Residues Imentioning
confidence: 99%
“…Absence of any significant decrease of cell growth in glucose medium in the presence of CCCP suggests that glucose transport is not dependent on TBDRs or other pmf-dependent processes in C. crescentus, and thus may be accomplished by passive diffusion via outer membrane porins (Nikaido, 1994;Shrivastava et al, 2011;Tamber & Hancock, 2003;van den Berg, 2012). OprB is a glucoseinduced porin, first identified in Pseudomonas aeruginosa, and known to transport a wide range of hydrophilic molecules, including carbohydrates, by facilitated diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…In a further turn of the screw, some plasmids deliver to the host novel functions that change their lifestyle (e.g., the thermal window of optimal viability) and even switch the order of preference of carbon source consumption (10)(11)(12). Spreading these properties in a population depends on plasmids' ability to move between different hosts.…”
Section: Promiscuous Plasmids Bear Key Host-independent Biological Fumentioning
confidence: 99%